Nilai Kemanusiaan di Film La La Land - Harahap, Nurul Fathya; Chitra, Bima Prana (Vernacular: Linguistics, Literature, Communication and Culture Journal, 2025)
This study aims to analyze the human values ​​contained in Damien Chazelle's La La Land movie. This movie not only shows a love story, but also depicts the struggle of life, sacrifice, dreams, and internal conflicts that are full of human values. This study uses a descriptive qualitative approach with a content analysis method to identify and understand the human messages presented in the narrative, characters, dialogues, and visualization of the movie. The results of the study show that La La Land presents various human values, such as the struggle to achieve dreams (human aspiration), sacrifice for love and career, courage to face failure, and appreciation for the process and effort. These values ​​are conveyed through the journey of the main characters, Mia and Sebastian, which depicts the dynamics between pursuing personal ambition and maintaining emotional relationships. This study concludes that La La Land is not only a musical movie, but also a medium that is full of human messages that are relevant to real life. These values ​​can provide inspiration and reflection for the audience to understand the importance of balance between dreams and social life.